Descrição de um novo espécime de pterossauro (Pterodactyloidea, Tapejaridae) da Formação Crato, Cretáceo Inferior da Bacia do Araripe (CE, Brasil) - Santos, Janiele Cruz (2020)
Pterosauria is a group of extinct vertebrates that lived during the Mesozoic Era. These arcosaurs had their first occurrence dating back to the Upper Triassic and lived until the end of the Cretaceous.They are traditionallydivided into two major groups: Rhamphorhynchoidea (basal, paraphyletic) and Pterodactyloidea (more derived, monophyletic). For the Araripe Basin, located in the Northeast of Brazil, so far 30 species of pterosaurs have been described. The Crato Formation presents a thick, finally laminated carbonate sequence of lacustrine origin, internationally recognized for having an abundant and well diversified fossil record. There is a diverse fauna of invertebrates and vertebrates, represented by arthropods, small fish, amphibians, lizards and pterosaurs. This work aims to describe the osteologya new specimen of pterosaur. From the analyses, morphological characteristics belonging to the Tapejaridae family were presented. The information present in this research increasesthe knowledge about the post-cranial anatomyof this group to the Araripe Basin